Ocorrência de nitrato nas águas subterrâneas do Sistema Aquífero Bauru em áreas rurais - Moura, Cinthia Cristine de [UNESP] (2014)
The Bauru Aquifer System (BAS) represents the most important aquifer in the western portion of the state of São Paulo, which is an excellent option for supplying water for rural properties. Monitoring of groundwater quality in the state of São Paulo, carried out by CETESB, has observed an increase in nitrate concentrations in BAS's groundwater. In many parts of the world, studies linked agricultural activities with nitrate contamination of groundwater, while in São Paulo state the extension of nitrate contamination still unknown, which has motivated the development of this research project. The main purpose of this study is to evaluate the concentrations of nitrate in BAS's groundwater beneath rural zone in the city of São José do Rio Preto and Bauru. Activities carried out include record of wells and economic activity in the farms, groundwater sampling for chemical analysis, statistical treatment of hydrochemical data and evaluation of the possible relations between observed nitrate concentrations and the activities developed in the propriety. Nitrate concentration higher than the limit for drinking water quality established by the Brazilian authorities (MS2914/2011) has observed only in two samples in São do Rio Preto for both campaigns and in three samples collected in the first campaign and two samples collected in the second campaign, in Bauru. Meanwhile evidences of nitrate contamination were detected in several samples, especially in properties where are developed just livestock and agricultural activities associated with livestock (mixed), suggesting that the major sources of nitrate are from in-situ sanitation and/or animal manure disposition, associated with high salinity waters. In proprieties where the agriculture is the main developed activities, groundwater present low mineralization, but there is a human influence, observed in the increases on nitrate and chloride concentration